The Dopaminergic Reward System and Leisure Time Exercise Behavior: A Candidate Allele Study. (9th March 2014) - Huppertz, Charlotte; Bartels, Meike; Groen-Blokhuis, Maria M.; Dolan, Conor V.; de Moor, Marleen H. M.; Abdellaoui, Abdel; van Beijsterveldt, Catharina E. M.; Ehli, Erik A.; Hottenga, Jouke-Jan; Willemsen, Gonneke; Xiao, Xiangjun; Scheet, Paul; et al.
Abstract : Purpose . Twin studies provide evidence that genetic influences contribute strongly to individual differences in exercise behavior. We hypothesize that part of this heritability is explained by genetic variation in the dopaminergic reward system. Eight single nucleotide polymorphisms (SNPs in DRD1: rs265981, DRD2: rs6275, rs1800497, DRD3: rs6280, DRD4: rs1800955, DBH: rs1611115, rs2519152, and in COMT: rs4680) and three variable number of tandem repeats (VNTRs in DRD4, upstream of DRD5, and in DAT1 ) were investigated for an association with regular leisure time exercise behavior. Materials and Methods . Data on exercise activities and at least one SNP/VNTR were available for 8, 768 individuals aged 7 to 50 years old that were part of the Netherlands Twin Register. Exercise behavior was quantified as weekly metabolic equivalents of task (MET) spent on exercise activities. Mixed models were fitted in SPSS with genetic relatedness as a random effect. Results . None of the genetic variants were associated with exercise behavior (P > . 02 ), despite sufficient power to detect small effects. Discussion and Conclusions . We did not confirm that allelic variants involved in dopaminergic function play a role in creating individual differences in exercise behavior. A plea is made for large genome-wide association studies to unravel the genetic pathways that affect this health-enhancing behavior.